Retreat Sites Shared by Two Liolaemus Lizard Species: Exploring the Potential Role of Scents - Ruiz Monachesi, Mario Ricardo (2020)
Some lizard species modulate the use of a retreat site based on the presence of scents from other individuals, behavior that requires scent recognition. Here, we investigated if two congeneric and syntopic lizards (adults of Liolaemus coeruleus and juveniles of L. ceii, which can be found sharing retreat sites in the wild) discriminate scents from each other during the pre-hibernation period. If the presence of heterospecific scents modulates sharing retreat sites, species would discriminate each other’s scents. Lizards were individually exposed to four treatments, which were enclosures with scents of (1) from the focal individual (own); (2) a conspecific of the same sex as the focal lizard; (3) a heterospecific of the same sex as the focal lizard; and (4) a control (i.e., enclosure with a clean substrate). Our results suggest that there is no heterospecific recognition. This finding was not due to an inability to chemo-assess scents, since both species exhibited self-recognition (recognition of their own scents) and juveniles of L. ceii also showed conspecific recognition. Although it might be advantageous for species to share retreat sites, chemical recognition of heterospecific scents does not modulate this behavior in these syntopic species.